Internal Issues in Private Education - Sheehan, Lourdes (Catholic Education: A Journal of Inquiry and Practice, 1999)
One of the keynote addresses at the Private Research Conference held at the University of Dayton in November of 1997 focused on “Internal Issues in private Education.” This paper addresses several salient points and then poses research questions related to this topic and to issues which embrace school participants school organizations and management, school climate and culture, and academic programs and support services in private schools.